2013
DOI: 10.1371/journal.pone.0073309
|View full text |Cite|
|
Sign up to set email alerts
|

Independent Component Analysis for Brain fMRI Does Indeed Select for Maximal Independence

Abstract: A recent paper by Daubechies et al. claims that two independent component analysis (ICA) algorithms, Infomax and FastICA, which are widely used for functional magnetic resonance imaging (fMRI) analysis, select for sparsity rather than independence. The argument was supported by a series of experiments on synthetic data. We show that these experiments fall short of proving this claim and that the ICA algorithms are indeed doing what they are designed to do: identify maximally independent sources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 76 publications
(60 citation statements)
references
References 16 publications
1
57
0
Order By: Relevance
“…However, Daubechies et al (2009) claimed that two ICA algorithms, InfomaxICA and FastICA, select for sparsity rather than independence. The follow-up work by Calhoun et al (2013) showed that the claims made in Daubechies et al (2009) were not supported by experimental evidence and the ICA algorithms are indeed identifying maximally independent sources (Calhoun et al, 2013). Our study focuses on using sparse modeling for fMRI analysis.…”
Section: Discussionmentioning
confidence: 95%
“…However, Daubechies et al (2009) claimed that two ICA algorithms, InfomaxICA and FastICA, select for sparsity rather than independence. The follow-up work by Calhoun et al (2013) showed that the claims made in Daubechies et al (2009) were not supported by experimental evidence and the ICA algorithms are indeed identifying maximally independent sources (Calhoun et al, 2013). Our study focuses on using sparse modeling for fMRI analysis.…”
Section: Discussionmentioning
confidence: 95%
“…Spatial Independent Component Analysis (ICA) of the reconstructed fMRI data and the original fully available fMRI dataset is performed via GIFT toolbox 2 . ICA is a data driven method that has been widely used in resting state fMRI to recover the set of spatially independent brain RSNs [38,39,40,41,42].…”
Section: Qualitative Analysismentioning
confidence: 99%
“…It assumes that the observed signals are mixtures of statistically independent sources [5]. Therefore, it aims to decompose the mixed signals into the independent sources.…”
Section: Problem Formulationmentioning
confidence: 99%
“…In order to produce physiologically interpretable robust features, ICA has been applied to brain imaging data. Successful application of ICA on fMRI can be attributed to sparsity [6] and statistical independence between the underlying sources [5].…”
Section: Problem Formulationmentioning
confidence: 99%